Reconciling Western and African philosophy : rationality, culture and communitarianism - Vitsha, Xolisa (Rhodes University, Faculty of Humanities, Department of Political Studies, 2002)
This thesis attempts to reconcile Western and African philosophy with specific reference to the issues of rationality, culture and communitarianism. It also discusses the post-Enlightenment, Western philosophical concept of liberal "atomism" and the primacy of the individual and the emergence of a communitarian critique in response. This thesis intends exploring how Western notions of individuality and the communitarian response can be reconciled with contemporary African philosophy and African communitarian thought in particular. To do this, it is necessary to explore the problem of liberal individualism and how African communitarianism might reinforce the Western communitarian critique. African communitarianism has a processual understanding of personhood that underpins its conception of the Self. In contrast to this view, Western communitarianism has a relational conception of the individual Self. Thus, this thesis argues that African communitarianism has a more profound understanding of the constitution of the Self. To demonstrate these claims, this study discusses notions of rationality which inform each of the philosophical traditions. This will enable a comparative analysis of the above-mentioned philosophical traditions with the intention of uncovering the concepts that provide the platform for their reconciliation.
Keywords: Philosophy, African; Africa -- Intellectual life; Philosophy, Comparative; Philosophy; Communitarianism; Self